Forecasting Energy Consumption of a House using Radial Basis Function Network - Saranya, N; Zoraida, B.S.E (International Journal of Computer Sciences and Engineering, 2025)
Electrical energy is used throughout the globe to power devices, appliances, and strategies of transportation used in everyday life. The uses of electricity are Residential uses, industrial uses, and Transportation. This paper targeted on Forecasting Energy Consumption of a House using historical information. The proposed work uses the Radial Basis Function (RBF) Network for forecasting the demand for energy consumption of a house using historical data. The result showed that the Radial Basis Function Network performs better than FeedForward BackPropagation Network (FFBPN), and Elman BackPropagation Network (EBPN) were compared with Mean Square Error (MSE) and accuracy values